Targeted bacterial conjugation mediated by synthetic cell-to-cell adhesions. Issue 22 (13th December 2022) - Robledo, Marta; Álvarez, Beatriz; Cuevas, Ana; González, Sheila; Ruano-Gallego, David; Fernández, Luis Ángel; de la Cruz, Fernando
Abstract: Genetic interventions on microbiomes, for clinical or biotechnological purposes, remain challenging. Conjugation-based delivery of genetic cargo is still unspecific and limited by low conjugation rates. Here we report an approach to overcome these problems, based on a synthetic bacterial adhesion system. Mating assemblers consist on a synthetic adhesion formed by the expression on the surface of donor and target cells of specific nanobodies (Nb) and their cognate antigen (Ag). The Nb–Ag bridge increased 1–3 logs transfer of a variety of plasmids, especially in liquid media, confirming that cell-cell docking is a main determinant limiting mating efficiency. Synthetic cell-to-cell adhesion allows efficient conjugation to targeted recipients, enhancing delivery of desired genes to a predefined subset of prey species, or even specific pathogenic strains such as enterohemorrhagic Escherichia coli (EHEC), within a bacterial community. The synthetic conjugation enhancer presented here optimizes plasmid delivery by selecting the target hosts with high selectivity. Graphical Abstract: